A new oleanane type triterpenoid and other constituents from the waterlogging tolerant plant Myricaria laxiflora. (October 2016) - Zhang, Kuo; Han, Mei-Jun; Wang, Ling; Liu, Shuai; Zhao, Xin-Fei; Shen, Wei-Yun; Mao, Hong-Qiang; Qin, Dan; Dong, Jin-Yan
Abstract: Myricaria laxiflora is an endangered evergreen shrub that is the only species in the genus Myricaria narrowly distributed in the Three Gorges region in China, which has a highly tolerant to waterlogging. The chemical investigation of M. laxiflora led to the isolation and the structural elucidation of nine compounds (1 –9 ), including one new oleanane type triterpenoid, (5 R, 8 R, 9 R, 10 R, 13 S, 17 S, 18 S ) 25, 28-dihydroxy- D -friedoolean-14-en-3-one (2 ). Their chemical structures were unambiguously elucidated by analysis of NMR and high resolution ESI mass spectroscopic data as well as by comparison with literature data, with the structure of1 supported by X-ray crystallography. All these compounds were reported for the first time in M. laxiflora. Besides, compounds1 and6 were not previously known in the genus Myricaria. Finally, compounds1 –9 were assumed to contribute to the survival of M. laxiflora under waterlogging stress by eliminating the reactive oxygen species (ROS). Highlights: A new oleanane triterpenoid, 25, 28-dihydroxy- D -friedoolean-14-en-3-one was isolated from Myricaria laxiflora. Nine compounds1 –9 were firstly isolated from Myricaria laxiflora. Two oleanane type triterpenoid1 and6 were not previously known in the genus Myricaria. This was the first report on the X-ray diffraction data of D -friedoolean-14-ene-3 α, 28-diol (isomyricadiol) (1 ).